Winners and Losers in the Liberalized Energy Retail Sector in Hungary: A Co-evolutionary Approach - Felsmann, Balázs (Theory, Methodology, Practice – Review of Business and Management, 2014)
This paper examines the recent history of the Hungarian energy trading market in a co-evolutionary framework. Hungary is characterized by a mixed ownership structure with mainly multinational incumbents in energy retail and distribution, while the wholesale is dominantly owned by state-owned companies. The legal framework also has dual characteristics, with free-market regulation for industrial consumers and a regulated price regime for households. Our research method follows a longitudinal approach from the period of market liberalization in 2008 until 2013. We identified strong relationship between the individual and sector performance of the trading companies and the current political ideology and institutional regime.